ILRI research on animal diseases in Africa - Focus, integration, and impact orientation - Randolph, Thomas F. (International Livestock Research Institute, 2011)
For the November 2011 'liveSTOCK Exchange' event at the International Livestock Research Institute (ILRI), Tom Randolph reflects on his experiences and work at ILRI on animal health issues.